Signal intensity changes of the posterior elements of the lumbar spine in symptomatic adults - Kosuke Sugiura; Toshinori Sakai; Fumitake Tezuka; Kazuta Yamashita; Yoichiro Takata; Kosaku Higashino; Akihiro Nagamachi; Koichi Sairyo (Spine Surgery and Related Research, 2017)
Introduction: Modic type 1 changes around the vertebral endplate of the lumbar spine are well known to indicate inflammation; however, the clinical significance of similar SCs of the posterior elements has not been elucidated. Methods: Six hundred ninety-eight MRIs of patients with complaints of low back/leg pain were retrospectively examined. Target SCs in this study were hypointensity on T1-WI and hyperintensity on T2-WI or short tau inversion recovery sequences showing the same signal patterns seen in Modic type 1 change of the lumbar posterior elements. We analyzed the (1) Prevalence, symptom, and age distribution of SCs, (2) Localization of SCs and their association with Modic type 1 changes, (3) Spinal level distribution of SCs, (4) Association between SCs and disc degeneration of the affected spinal level, and (5) Association between SCs and radiological changes (spondylolisthesis, scoliosis). Results: (1) Among 698 adult patients, 36 (16 men, 20 women) exhibited SCs (5.2%). No SCs were identified in patients age <40 years. (2) Of the 36 SCs, 9 (25%) were localized at a single spinal level, while 27 (75%) were found at neighboring spinal levels across the facet joint. Thirteen SCs (36.1%) had continuity with Modic type 1 changes around the vertebral endplate, while 23 (63.9%) were localized to the posterior elements. (3) SCs were frequently identified in the lower lumbar spine below the L4 level. (4) More than 80% of the SCs involved disc degeneration. (5) Spondylolisthesis was associated with 93% of SCs in double-level, and scoliosis was associated with SCs in unilateral side. Conclusion: The prevalence of SCs in symptomatic adults was 5.2%. On the basis of observed disc degeneration, 75% of SCs were considered to indicate inflammation or bone marrow edema around the facet joint.